Virilité, métier et rapport aux risques professionnels : le cas de travailleurs de la sous-traitance - Paul Bouffartigue; Jean-René Pendariès; Jacques Bouteiller (Perspectives Interdisciplinaires sur le Travail et la Santé)
Industrial subcontracting is associated with a deterioration in occupational health and safety. A survey among subcontracting male workers in heavy industry shows that they are highly exposed to work instability and difficulty, with frequent impacts on their health. Risk awareness does exist, but many mechanisms attenuate it, including persistence of defensive strategies, based on virility and the profession. But work is not just a « health impact factor », it is also a « health factor », through professionalism and cooperation practices within working groups. Work is also a « health revealer », which is also constructed elsewhere, through health selection effects. Finally, work regulates health and aging, via promotional career paths that can remove workers from the most difficult and dangerous work situations.